Chemical Photocatalysis. Edited by Burkhard König. Issue 44 (17th September 2013) - Hoffmann, Norbert
<x xml:space="preserve">Abstract</x> De Gruyter, Berlin, 2013. 386 pp., hardcover, € 139.95.—ISBN 978‐3110269161<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>